The utilization of RTK-GPS for real-time structural health detection - Nordin, Zuhaidah; Yahya, Mohd. Hafiz; Wan Mohd. Akib, Wan Aziz; Mat Amin, Zulkarnaini (2008)
As safety precautions, the need for rapid assessment of the state of large engineering structure after extreme events such as earthquake, tsunami, typhoon or related wind effects is highly demanded. Compared to other often used practices such as acceleration integration method, laser distance gauge method and total station method, it is noted that GPS through static surveying technique is capable of providing 0.05 Hz of sampling frequency with location precision of 5~10 mm. Apparently, with the advent of Real-Time Kinematic (RTK-GPS) technique, deformations of various structures such as dams, wide span bridges, highways and high rise buildings can be monitored in real-time mode with 3D positioning accuracy of 10 mm Â± 1 to 2 ppm (horizontally) and 15-20 mm Â± 2 ppm (vertically). This paper therefore leads to a better understanding on RTK-GPS through simulation test made on a bridge in Universiti Teknologi Malaysia (UTM) campus. For the purpose of real-time structural health detection, well-calibrated GPS Trimbleâ„¢ 4800 dual-frequency receivers and Pacific Crestâ„¢ radio modems were used in this study. By applying static survey mode to determine true coordinates in which will be used latter as â€œreferenceâ€?, the test was then conducted in real-time using RTK-GPS mode. It is noted that GPS through the utilization of RTK-GPS is potentially capable of being deployed as an effective tool in structural health detection.